2017
DOI: 10.1016/j.spa.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel sequential Monte Carlo samplers

Abstract: In this article we consider the approximation of expectations w.r.t. probability distributions associated to the solution of partial differential equations (PDEs); this scenario appears routinely in Bayesian inverse problems. In practice, one often has to solve the associated PDE numerically, using, for instance finite element methods and leading to a discretisation bias, with the step-size level h L . In addition, the expectation cannot be computed analytically and one often resorts to Monte Carlo methods. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
169
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(172 citation statements)
references
References 18 publications
0
169
1
Order By: Relevance
“…More recently, it has been shown that the MLMC telescoping summation can accelerate the computation of posterior expectations when using MCMC [29,32] or SMC [12].…”
Section: Calculate Acceptance Probabilitymentioning
confidence: 99%
“…More recently, it has been shown that the MLMC telescoping summation can accelerate the computation of posterior expectations when using MCMC [29,32] or SMC [12].…”
Section: Calculate Acceptance Probabilitymentioning
confidence: 99%
“…For the solution of Bayesian inverse problems, there are multi-stage MCMC methods that aim to reduce the number of high-fidelity model evaluations by first screening proposed moves with lowfidelity models [14,22]. Another line of work builds on hierarchies of low-fidelity models, typically derived from different discretizations of partial differential equations (PDEs) underlying the high-fidelity model, to reduce sampling costs [4,20,31].…”
Section: Introductionmentioning
confidence: 99%
“…For Bayesian Inverse Problems a multilevel MCMC method has been introduced in [18]. Multilevel Sequential Monte Carlo is introduced in [4] and further discussed in [3,17,16]. Both the multilevel MCMC and multilevel SMC use coarse PDE discretisations for variance reduction with the help of a telescoping sum expansion.…”
Section: Introductionmentioning
confidence: 99%
“…This update scheme is consistent with the adaptive bridging and tempering discussed in §3. 4. Finally, in §5 we present numerical experiments for a test problem in 2D space.…”
Section: Introductionmentioning
confidence: 99%